In situ elemental analyses of living biological specimens using ‘NanoSuit’ and EDS methods in FE-SEM - Takaku, Yasuharu (Sci Rep, 2020)
Energy dispersive X-ray spectroscopy (EDS) carried out alongside scanning electron microscopy (SEM) is a common technique for elemental analysis. To investigate “wet” biological specimens, complex pre-treatments are required to stabilize them under the high vacuum conditions of high-resolution SEM. These often produce unwanted artifacts. We have previously reported that the polymerization of natural surface substances on organisms by the electron beam of the SEM setup or by plasma irradiation causes a nano-scale layer to form—called a “NanoSuit”—that can act as a barrier and keep organisms alive and hydrated in a field-emission SEM system. In the study reported herein, we examined the suitability of the NanoSuit method for elemental analyses of biological specimens by EDS. We compared experimental results for living Drosophila larvae and Aloe arborescens specimens prepared by the NanoSuit method and by conventional fixation. The NanoSuit method allowed accurate detection of the elemental compositions at high resolution. By contrast, specimens prepared by the conventional fixation method displayed additional EDS signals corresponding to the elements in the chemicals involved in the fixation process. Our results demonstrate that the NanoSuit method is useful for studying hydrous samples via EDS and SEM, particularly in biological sciences.